Intraosseous Sliding Plate Fixation Used in Double Osteotomy Bunionectomy. (January 2019) - Bennett, Gordon L.; Klaus, Derek; Shemory, Scott; Sabetta, James A.
Background: Distal chevron metatarsal osteotomy bunionectomy is a commonly performed procedure for the treatment of mild to moderate hallux valgus. We continue to use the intraosseous sliding osteotomy plate system for fixation of the distal metatarsal osteotomy. With the addition of the Akin osteotomy, we are able to obtain reliable, reproducible correction with better cosmesis and increased patient satisfaction for more advanced deformities. Methods: We prospectively evaluated 138 (145 feet) consecutive patients who underwent double osteotomy bunionectomy using the intramedullary plate system and 3.2-mm cannulated screw system. The senior author performed all operative procedures. Patients were evaluated preoperatively, postoperatively, and at the final follow-up using the American Orthopaedic Foot & Ankle Society (AOFAS) forefoot scoring system. Results: All osteotomy sites of operatively corrected feet healed. There were no hardware failures. A small number of patients complained of stiffness and pain related to the hardware. All patients dramatically improved their AOFAS scores compared with preoperative values. The hallux valgus angle was corrected by a mean of 17.3 degrees (range, 10 to 20 degrees), and the intermetatarsal angle was corrected by a mean of 6.8 degrees (range, 5 to 9 degrees). Conclusion: Chevron osteotomy paired with an Akin osteotomy (double osteotomy bunionectomy) resulted in excellent function and pain relief. We continue to recommend the use of the intramedullary plate system and 3.2-mm cannulated screw system because of its low profile, reliability of fixation, and relative ease of use. Level of Evidence: Level III, retrospective comparative series.